2003
DOI: 10.2139/ssrn.1923138
|View full text |Cite
|
Sign up to set email alerts
|

Growth Setbacks in New Firms

Abstract: This paper examines setbacks in the early growth of new firms. Growth interruptions mark the unfolding, cumulative processes of firm growth overlooked in standard studies that use cross sectional methods. To probe for possible patterns in growth setbacks, we examined a cohort of 200 high technology firms founded in about 1990 and analysed the growth paths of survivors. Simple compression techniques yielded seven types of growth turning points. Growth setbacks are the norm even among firms with better growth re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Our empirical study revealed that even in an elite sample of young fast-growing firms, most firms face turning points in their life course (cf. Garnsey et al, 2003). These turning points are often caused by problems and constrain growth, and force the firm to focus again after a resource or competence shortage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our empirical study revealed that even in an elite sample of young fast-growing firms, most firms face turning points in their life course (cf. Garnsey et al, 2003). These turning points are often caused by problems and constrain growth, and force the firm to focus again after a resource or competence shortage.…”
Section: Discussionmentioning
confidence: 99%
“…We start with quantitative evidence which points to uneven and discontinuous growth in new firms in our sample (see Garnsey et al (2003) for a discussion of the methods used). Though this evidence does not directly map developmental processes, it does show that turning points, interruptions and setbacks are common in the growth paths of new firms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such re-investment is more difficult when lower levels of slack financial resources exist in the firm Katila and Shane, 2005). In contrast, however, the less financial resources that are available, the more a firm has to care about generating short-term revenues to fuel its operations (Garnsey, 1998;Garnsey and Heffernan, 2005). Here, firms can earn immediate revenues by being customer oriented (Bhidé, 2000).…”
Section: Antecedents Of Entrepreneurial and Customer Orientationmentioning
confidence: 99%